Event Extraction from Twitter using Scoring Function and LDA - Gupta, Monika; Gupta, Parul (International Journal of Computer Sciences and Engineering, 2025)
Extracting and interpreting information from user generated content is a current topic in the scientific community and in the business world. Furthermore, data with a spatial component are even more important. This is proved by the numerous web applications that deal with processing and visualization of user generated content. The task of this extraction is to collect major life events in the form of retrievable entries that include structured data about major life event name, location and time which are often, categorized by complex, and nested structures involving ambiguous entities.